Feasibility Study of a Solar Powered Semi-Submarine (KMP. Mnaibori) as a Model of Sustainable Marine Ecotourism in Raja Ampat - Yani Nurita Purnawati; Andreas Pujianto; Asthervina Widyastami Puspitasari; Wenty Kurniati; Sri Wahyuni Firman; Egbert Josua Sirait (Politeknik Negeri Sambas, 2025)
This study describes the KMP. Mnaibori, a 14-meter semi-submarine catamaran designed for the waters of Raja Ampat as a model of sustainable marine ecotourism. The objectives are to present the vessel’s design specifications, integrate a hybrid solar–energy system, and assess the financial feasibility and strategic aspects of its development. The methodology includes technical design analysis based on stability, comfort, and underwater observation experience; solar power system performance estimation using the peak sun hours and energy loss factor approach; and financial analysis using Payback Period (PP), Net Present Value (NPV), Profitability Index (PI), Internal Rate of Return (IRR), Break-Even Point (BEP), and Return on Investment (ROI) with a 12% discount rate over a 5-year horizon. The results show that with a solar panel area of 49 m² (38 modules @200 W), the system can generate 21.66 kWh per day. Economically, the project is feasible with a positive NPV of IDR 4.44 billion, a BEP at 12.11 passengers/day (33.6% occupancy), ROI of 49.85% per year, and IRR between 42–45%. SWOT analysis highlights the vessel’s strengths in innovative design and energy efficiency, opportunities in ecotourism growth and green financing support, and challenges related to fuel dependency and weather variability. Development strategies are directed toward service differentiation, solar energy optimization, and enhancing local maintenance capacity.